Developing a protocol to identify and prioritize research questions for psoriasis: a James Lind Alliance Priority Setting Partnership. (1st June 2018) - Majeed‐Ariss, R.; McPhee, M.; Bundy, C.; Griffiths, C.E.M.; Young, H.
Summary: Psoriasis is a common condition that affects over two million people in the UK and causes red, flaky patches of skin which can sometimes feel sore or itchy. People with psoriasis can be affected by their disease physically, emotionally and socially. There are many unanswered questions about psoriasis. To find out what the most important questions are, a Psoriasis Priority Setting Partnership PSP is being carried out now. The PSP involves patients, families, carers and healthcare professionals working together to follow a process outlined by the James Lind Alliance. The first step is for all groups with an interest in psoriasis to complete a survey about what they think the important research questions are. Survey responses are then checked against existing evidence. Questions raised in the surveys, but which have already previously been answered, will be shared with relevant organisations who may consider how this information can be better shared with clinicians, patients and their families. Questions raised in the surveys, which have not already been answered will be compiled into a list. This list will be sent round to stakeholders in a second survey where they will be ordered by importance. At a final workshop, a 'top ten' list of unanswered questions will be agreed by patients, their carers and health professionals. This 'top ten' list will be shared widely with psoriasis researchers and funders, to encourage research that focuses on tackling the key issues which really matter to patients, families, carers and healthcare professionals.